2020
DOI: 10.3390/ma13163534
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Hollow Aluminium Oxide Microballoons during Machining of AZ31 Magnesium Syntactic Foam

Abstract: The role played by hollow ceramic thin-walled aluminium oxide microballoons on the shear deformation characteristics of AZ31 Magnesium syntactic foam is studied through high-speed machining. The ceramic microballoons embedded in the AZ31 matrix provides the necessary stiffness for these novel foams. The effect of hollow ceramic microballoon properties, such as the volume fraction, thin wall thickness to diameter ratio, and microballoon diameter, profoundly affects the chip formation. A novel force model has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Magnesium syntactic foam billets were manufactured through the squeeze casting method [11]. During the casting process, the stirrer RPM was maintained between 450-500 RPM for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnesium syntactic foam billets were manufactured through the squeeze casting method [11]. During the casting process, the stirrer RPM was maintained between 450-500 RPM for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that an increase in the volume fraction of hollow microspheres increases the hardness, compression yield strength, peak compression strength, and plateau strength of the syntactic metal foams [7][8][9][10]. The coarser the average size of hollow reinforcements is, the lower the hardness of the magnesium closed-cell foam [11,12]. The mechanical properties of aluminum-based syntactic foam are shown to be comparable to the base alloy under cryogenic conditions [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These reinforced materials have a relatively large density, which is not conducive to providing large buoyancy for deep-sea exploration equipment [ 10 , 11 ]. The introduction of the low-density aerogel is more conducive to reducing the density of foam to improve the overall performance and reduce the energy consumption of the submersible [ 12 , 13 , 14 ]. In this experiment, the aerogel reinforced hollow epoxy macro-spheres (AR-HEMS) was prepared innovatively by ‘the rolling ball method,’ and the same rolling time and method were adopted to make the aerogel powder wrapped around the EPS beads evenly [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxide particles, such as Al 2 MgO 4 , Al 2 O 3 , MgO, and SiO 2 , observed in aluminum alloys are extremely hard concerning the matrix and their treatment represent a complex technological challenge [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The addition of microparticles in metals, combined with proper thermomechanical treatment, can be used to increase the mechanical properties in a beneficial sense [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%